Algorithmic Approach for the Application of Graphic Standards in the BIM Environment (diségno, 2021)
In the era of digital connection, the construction industry is crossing a transition that involves numerous aspects, related, among others, to the representation of the building artifact. Information and Communication Technologies (ICTs) in the construction process stimulate the adoption of innovative methods and tools aimed at communicating a design idea, shifting the focus from the digital drafting machine to the information model. The adoption of Building Information Modeling (BIM) is triggering a radical inversion of perspective, such that the development of a parametric 3D model allows the generation of a series of coordinated drawings, avoiding information redundancy and consequent inconsistencies. Traditionally, the production of design content takes advantage of standards and graphic conventions, inherited from information modeling tools. The contribution aims to develop a critical approach on the current capabilities of collaborative BIM models to produce such documents, as part of the construction process. This study is part of a broad field of research focused on optimizing the building process by improving the connection between tradition and innovation in the science of representation.
Keywords: Building Information Modeling; Visual Programming Language; graphic standards; connected BIM; algorithms